Intrasinus Thrombolysis for Cerebral Venous Sinus Thrombosis: Single-Center Experience - Guo, Xinbin; Sun, Jiachen; Lu, Xiaoke; Guan, Sheng (Frontiers in Neurology, 2019)
Objective The purpose of this research was to study the safety and efficacy of intrasinus thrombolysis in patients with cerebral venous sinus thrombosis unresponsive to conventional heparin therapy. Methods 156 CVST patients were treated using interventional thrombolysis in our center from January 2010 to June 2018. Clinical data, including duration of symptoms, indications and outcome of IST were retrieved and outcomes were analyzed. DSA or MRV was used to assess the recanalization after thrombolysis. mRS was used to evaluate the outcome at admission, discharge and follow-up. Results 91.38% of patients obtained functional independence (mRS 0-2). The mRS score was 0-2 in 120 patients (76.92%, 120/156) at the time of discharge. Seven patients succumbed during hospitalization. MRV examination was performed in 149 patients, and the results showed that the venous sinus of 112 patients (75.17%) was completely recanalized, the venous sinus was partially recanalized in 28 patients (18.79%) and 9 patients (6.04%) had no recanalization at the time of discharge. 116 patients were followed up at least for 6 months, 89 patients (76.72%) were completely recanalized, 21 patients (18.1%) were partially recanalized, and 6 patients (5.17%) were not recanalized. Conclusion IST may be more effective than systemic heparin anticoagulation in moribund and unresponsive patients despite of the risk of hemorrhage. Large randomized controlled trials are required to further evaluate this issue.ndence (mRS 0-2). The mRS score was 0-2 in 120 patients (76.92%, 120/156) at discharge. Seven patients succumbed during hospitalization. MRV examination was performed in 149 patients, and the results showed that the venous sinus of 112 patients (75.17%) was completely recanalized, the venous sinus was partially recanalized in 28 patients (18.79%) and 9 patients (6.04%) had no recanalization at discharge. 116 patients were followed up at least for 6 months, 89 patients (76.72%) were completely recanalized, 21 patients (18.1%) were partially recanalized, and 6 patients (5.17%) were not recanalized. Conclusion IST may be more effective than systemic heparin anticoagulation in moribund and unresponsive patients despite the potential for bleeding manifestations. Large randomized controlled trials are required to further clarify this issue.